2016
DOI: 10.7287/peerj.preprints.2309v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic, ecological and physiological responses of ringed seals to an abrupt decline in sea ice availability

Abstract: To assess whether demographic declines of Arctic species at the southern limit of their range will be gradual or punctuated, we compared large-scale environmental patterns including sea ice dynamics to ringed seal (Pusa hispida ) reproduction, body condition, recruitment, and stress in Hudson Bay from 2003-2013. Aerial surveys suggested a gradual decline in seal density from 1995-2013, with the lowest density occurring in 2013. Body condition decreased and stress (cortisol) increased over time in relation to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…In contrast, southern seals invested more into offspring at an earlier age to take advantage of more productive environmental conditions (Stearns, ). In the south, seals cycled seasonally from high blubber storage (up to 60% of body mass) to very low body condition (30% blubber) that likely threatened their survival (Ferguson et al, ; Ferguson et al, ; Young & Ferguson, ). Progeny born into southern regions likely encountered good feeding conditions during the open‐water season allowing for faster growth and earlier reproduction, with shorter longevity as a tradeoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, southern seals invested more into offspring at an earlier age to take advantage of more productive environmental conditions (Stearns, ). In the south, seals cycled seasonally from high blubber storage (up to 60% of body mass) to very low body condition (30% blubber) that likely threatened their survival (Ferguson et al, ; Ferguson et al, ; Young & Ferguson, ). Progeny born into southern regions likely encountered good feeding conditions during the open‐water season allowing for faster growth and earlier reproduction, with shorter longevity as a tradeoff.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to measure maximum lifespan and instead used median age of seals harvested in autumn (August–December) as an index to compare age distribution of seals in the north versus south. Previous research has indicated that the autumn hunt during the open‐water season provides samples that are representative of the population age‐sex distribution (Ferguson, Young, Yurkowski, Anderson, & Willing, ).…”
Section: Methodsmentioning
confidence: 99%
“…, , Ferguson et al. , ), but because we were using it as a proxy for the availability of a suitable pupping and nursing substrate, we used this definition and then studied sensitivity to it.…”
Section: Methodsmentioning
confidence: 99%
“…Climate change is expected to affect ringed seals in myriad ways, including effects due to changing ecosystem productivity, food availability, and predation pressure from polar bears (Laidre et al 2008, Kelly et al 2010. In addition to these projected gradual changes, episodic events, including disease, can cause abrupt demographic changes on shorter timescales (Ferguson et al 2017). We do not attempt to capture all of these factors here, but rather study the implications of two known mechanisms of demographic change (Kovacs et al 2011).…”
Section: Ringed Seal Populations Past and Futurementioning
confidence: 99%
See 1 more Smart Citation